2019
DOI: 10.1016/s2213-2600(19)30137-7
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric tuberculosis transmission outside the household: challenging historical paradigms to inform future public health strategies

Abstract: Tuberculosis is a major cause of death and disability among children globally, yet children have been neglected in global tuberculosis control efforts. Historically, tuberculosis in children has been thought of as a family disease, and because of this, household contact tracing of children after identification of an adult tuberculosis case has been emphasised as the principal public health intervention. However, the population-level effect of household contact tracing is predicated on the assumption that most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 48 publications
4
51
0
1
Order By: Relevance
“…[29] Evidence increasingly shows that young children (<5 years old) are predominantly exposed to infectious TB outside their immediate household. [17] A high prevalence of latent TB infection among this group is indicative of intense community transmission and high prevalence of undiagnosed infectious TB, [30] meaning that urgent public health action is required to increase case detection and protect vulnerable groups and individuals. We are evaluating an intervention to protect household contacts and improve TB free survival in contacts of TB index patients in the parent cluster randomised trial; results will be reported once the trial has concluded.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…[29] Evidence increasingly shows that young children (<5 years old) are predominantly exposed to infectious TB outside their immediate household. [17] A high prevalence of latent TB infection among this group is indicative of intense community transmission and high prevalence of undiagnosed infectious TB, [30] meaning that urgent public health action is required to increase case detection and protect vulnerable groups and individuals. We are evaluating an intervention to protect household contacts and improve TB free survival in contacts of TB index patients in the parent cluster randomised trial; results will be reported once the trial has concluded.…”
Section: Plos Onementioning
confidence: 99%
“…[13][14][15] The evidence for the effectiveness and cost-effectiveness of household contact screening and treatment in sub-Saharan Africa is limited [16] because of the uncertainty over the role of community transmission outside the household. [17] However, in high-income settings public health approaches to TB contact-tracing have prioritised the most susceptible individuals and those with the greatest cumulative exposure for preventive interventions. [18] In high HIV prevalence settings, there remains considerable uncertainty around which index case-, household contact-, and community-level factors that are most important in determining risk of TB infection.…”
Section: Introductionmentioning
confidence: 99%
“…We found that 8% of TB infections among children 5-11 years old and 4% among adolescents (11-19 years) were attributable to a known household TB contact, which is consistent with prior studies that found on a population-level that household transmission only accounted for a small proportion of TB infections in children. [5,25] Our estimates are slightly lower than estimates of 10-30% published in prior studies [5,25], and this is likely because: (1) our sample includes older children and adolescents, whereas prior estimates were from children under the age of five and (2) our estimates likely under-estimates the PAF of household transmission as under-diagnosis of TB disease in rural areas of East Africa is common, and our estimate does not account for household transmission from undiagnosed household contacts.…”
Section: School and Community-level Factorsmentioning
confidence: 99%
“…Tuberculosis (TB) kills more people than any other infectious disease and halting transmission of Mycobacterium tuberculosis is essential to reducing the global burden of disease. However, in high-incidence settings, it is unknown where and between whom the majority of transmission occurs 24 and therefore where to focus interventions. Patterns of M. tuberculosis genetic and genomic variation are frequently used to identify potential recent transmission events.…”
Section: Introductionmentioning
confidence: 99%